Cover Feature: Cyanine‐Like Boronic Acid‐Derived Salicylidenehydrazone Complexes (Cy‐BASHY) for Bioimaging Applications (Chem. Eur. J. 62/2020). Issue 62 (1st October 2020) - Santos, Fábio M. F.; Domínguez, Zoe; Fernandes, João P. L.; Parente Carvalho, Cátia; Collado, Daniel; Pérez‐Inestrosa, Ezequiel; Pinto, Maria V.; Fernandes, Adelaide; Arteaga, Jesús F.; Pischel, Uwe; Gois, Pedro M. P.
Abstract : Boronic acid derived salicylidenehydrazone (Bashy) complexes can be designed as bright fluorescent dyes with tunable emission in the red spectral window. The image shows the structural development from parent Bashy towards cyanine‐like π‐expanded Bashy dyes that can be employed for the bioimaging of astrocytes. Astrocytes are star‐shaped cells that perform vital neurochemical functions. They are represented in the shown cellular structures. More information can be found in the Communication by U. Pischel, P. M. P. Gois, et al. on page 14064 .